2014
DOI: 10.2147/ijn.s68526
|View full text |Cite
|
Sign up to set email alerts
|

Silk fibroin nanoparticles constitute a vector for controlled release of resveratrol in an experimental model of inflammatory bowel disease in rats

Abstract: Purpose We aimed to evaluate the intestinal anti-inflammatory properties of silk fibroin nanoparticles, around 100 nm in size, when loaded with the stilbene compound resveratrol, in an experimental model of rat colitis. Methods Nanoparticles were loaded with resveratrol by adsorption. The biological effects of the resveratrol-loaded nanoparticles were tested both in vitro, in a cell culture of RAW 264.7 cells (mouse macrophages), and in vivo, in the trinitrobenzenesulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 39 publications
4
30
0
Order By: Relevance
“…These regulatory effects were not accompanied by changes in ZO-1 or occludin protein levels (Buda et al, 2012). Expression of TFF-3 is downregulated in intestinal inflammation (Lozano-Pérez et al, 2014), as observed in the present study. In connection with this, here we show that EcN OMVs increase colonic expression of this bioactive peptide involved in epithelial protection and repair (Podolsky et al, 2009), and preserve the damaged colonic cytoarchitecture of the mucosa in colitic mice.…”
Section: Discussionsupporting
confidence: 88%
“…These regulatory effects were not accompanied by changes in ZO-1 or occludin protein levels (Buda et al, 2012). Expression of TFF-3 is downregulated in intestinal inflammation (Lozano-Pérez et al, 2014), as observed in the present study. In connection with this, here we show that EcN OMVs increase colonic expression of this bioactive peptide involved in epithelial protection and repair (Podolsky et al, 2009), and preserve the damaged colonic cytoarchitecture of the mucosa in colitic mice.…”
Section: Discussionsupporting
confidence: 88%
“…Sirt1 activator resveratrol has been shown to attenuate the progression of nonalcoholic fatty liver disease (Faghihzadeh et al 2014) and inflammatory bowel disease (Lozano-Perez et al 2014). Considerable evidences indicated that Sirt1 is protective against a variety of kidney injury including LPS induced AKI, ischemia-reperfusion renal injury and diabetic nephropathy by suppressing kidney inflammation and down-regulating inflammatory signaling (Gao et al 2014;Hao and Haase 2010;Khader et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of IBD, RES administration was very effective in reducing mucosal inflammation via inhibition of malondialdehyde and increase of glutathione peroxidase activities, respectively [239][240][241][242][243][244]. Furthermore, in the above models, decrease in neutrophil infiltration and proinflammatory cytokine release and increase in number of Bifidobacteria and Lactobacilli with reduction of intestinal wall fibrosis have been observed [239][240][241][242][243][244].…”
Section: Allergy and Autoimmune Diseasesmentioning
confidence: 90%